TEACHER AS A MAIN SUBJECT OF THE EDUCATIONAL REFORM - Andrey A. Verbitsky (Высшее образование в России)
The purpose of the paper is to analyze the factors, which prevent a university teacher from becoming a real subject of the educational reform. Methods: analysis of the documents about the reform, empirical experience of realization of the main areas of the reform. The article shows that: 1) it is not productive to integrate innovations into the traditional educational system; 2) successful reform requires an adequate psycho-pedagogical basis; 3) the theory of contextual education can serve as a conceptual basis for the educational reform; in this case a university teacher will have a clear guideline which decisions to takewhile carrying out the educational reform.